Regulatory Compliance and Islamic Business Ethics in Umrah Administration: Rethinking the Centrality of Pilgrim Protection - Mahmudi Affan Rangkuti; Hendri Tanjung; Indupurnahayu Indupurnahayu; Trisiladi Supriyanto (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2026)
Purpose:This article rethinks pilgrim protection as the normative core of Umrah administration by examining whether regulatory compliance and Islamic business ethics function as an integrated governance framework or remain disconnected in practice. It positions pilgrim welfare, financial security, and spiritual integrity as the primary criteria for assessing the legitimacy of Umrah services.Design/Methodology:The study employs a qualitative socio-legal approach combined with normative ethical analysis. It examines Indonesia’s regulatory framework for Umrah administration and the operational role of digital oversight systems as instruments of monitoring and reporting. Compliance is interpreted through maqasid-oriented principles of Islamic business ethics, drawing on regulatory provisions and documented patterns of administrative problems to evaluate protection outcomes.Findings:The findings indicate persistent structural weaknesses in compliance quality and fragmented oversight, reflected in recurring issues such as system misuse and cases of pilgrim abandonment. These patterns demonstrate that procedural compliance does not automatically translate into substantive pilgrim protection. While strengthening data-driven supervisory systems is necessary, it remains insufficient without robust internal compliance capacity and accountable service standards.Practical Implications:This article offers a protection-centered analytical framework that bridges legal compliance theory and Islamic business ethics by reframing pilgrim protection as measurable governance substance rather than a symbolic commitment. It contributes a conceptual shift from form-based compliance to outcome-oriented ethical accountability in faith-based service administration.Originality/Value:The study recommends integrating sharia-compliance guidance into digital oversight mechanisms, strengthening transparency and public accountability, and developing fair dispute-resolution procedures to realign industry incentives with effective pilgrim protection and public trust.